My secretly hot husband. 4 - Jungyeon; Jungyeon; Nam, Gabi (Ize Press, 2025)
Though the trade war against Belaire was a resounding victory, Letitia barely has time to celebrate. With the immediate threat removed, the issue of her divorce with Erden resurfaces, and it's made far worse by the greedy nobles who flock to Halstead to demand her hand in remarriage. Letitia would much rather be out fighting devils than dealing with this nonsense, so she decides to do just that! Her plan is to infiltrate a secretive village and learn more about the sinister cult controlling it...if she can stop getting distracted by the unmasked Erden accompanying her!